Advancing sustainable lactic acid production: a mini review of biomass substrates, fermentation techniques, and industrial applications - Jasni, Ainil Hawa; Azmi, Azlin Suhaida; Mohamad Puad, Noor Illi; Ali, Fathilah; Ahmad Nor, Yusilawati (Persatuan Saintis Muslim Malaysia (PERINTIS), 2025)
Lactic acid (LA) has garnered global recognition for its versatile industrial applications, especially as a precursor to polylactic acid (PLA), a biodegradable polymer. This review comprehensively explores sustainable LA production using Rhizopus sp., with emphasis on the utilization of lignocellulosic agricultural residues as low-cost carbon sources. Conventional substrates such as glucose offer high yields but are economically and environmentally unsustainable. Instead, agro-wastes like empty fruit bunches, cocoa pod husks, cassava peels, coconut husks, and banana peels are rich in cellulose and hemicellulose, making them promising feedstocks. However, their complex structures necessitate pretreatment methods, including ethylenediamine (EDA) delignification, to enhance fermentability. The morphology of Rhizopus—pellet versus filamentous form—further influences LA yields, with pelletized forms offering higher productivity. Morphological control through fermentation parameters and neutralizing agents (e.g., CaCO₃) has shown significant effects on LA synthesis. This review emphasizes the need for integrated approaches combining biomass pretreatment, optimized fermentation conditions, and morphology control to improve LA yields. Ultimately, advancing sustainable fungal LA production supports waste valorization, circular economy goals, and green technology development in agriculture and industry